Community Perceptions about Participating in Urban Park Establishment in Ulaanbaatar City, Mongolia - Bayarmaa Enkhbold (MDPI AG, 2021)
Urban parks are essential for communities to maintain and improve health, culture, and quality of life. However, Ulaanbaatar, the capital of Mongolia, faces a shortage of urban parks due to overpopulation and unplanned land use. A good community-based strategy can help urban park planners and decision-makers understand residents’ needs. It can also improve livability and the urban environmental conditions at large. This paper attempts to understand residents’ perceptions about participating in urban park establishment and maintenance. As the past studies showed a lack of community participation in urban planning in Ulaanbaatar, it attempts to determine the extent to which residents perceive urban park benefits, the importance of community participation, preferred types of contribution, and willingness to contribution land in establishing urban parks in their neighborhood. In doing so, it identifies socio-demographic factors that influence their willingness to participate and contribute. A total of 600 paper-based questionnaires were randomly distributed among ger and apartment residents, and only 535 were analyzed. The result shows that approximately 73% of the respondents considered community participation very important for establishing urban parks in their neighborhood. Most respondents perceived urban park benefits as playgrounds for children, and relaxation and recreation. Respondents’ education and housing type were found significant in overall willingness to participate in park establishment and maintenance, whereas marital status and land size were observed statistically significant in the willingness of sharing some portions of their lands for park establishment in the ger area.